KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI SISTEM PRODUKSI BERSIH PADA AGROINDUSTRI KARET REMAH - Hasibuan, Sawarni (Universitas Djuanda Bogor, 2011)
Cleaner production is not only about changing raw materials, processes and products. It is also about changing attitudes and behaviour of all stakeholder. An understanding of the dynamics of change within and external organisations undertaking cleaner production can help to improve the success for implementation. The purpose of this study was to provide insight into the range of key factors that are potentially relevant to the success of cleaner production implementation on crumb rubber industry based on expert opinion and organizational perception. Factor analysis techniques with principal component and prospective analysis were aplied to extract that factors, while correlation analysis was used to inference the influence the organizational factors with cleaner producion performance. Principal component analysis resulted 13 factors, namely: internal communication, evaluation tools, environmental benefit, employee ability, profesional team, incentive system, cleaner prodution centre, community consultation, regulation, operational policy, environmental investment, green consumers, and environment requisite. The correlation of those factors with cleaner production performance at crumb rubber industry was not good (rs < 0,5). Based on prospective analysis, critical factors of cleaner production system implementation were culture, raw material, crumb rubber product, regulation, economic benefit, cleaner production information, environmental management system, and global market trend.KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHIIMPLEMENTASI SISTEM PRODUKSI BERSIHPADA AGROINDUSTRI KARET REMAH